Investigation of phytochemical composition, evaluation of antioxidant, antibacterial activities and toxicity study of Emblica officinalis and Terminalia bellirica fruits - Badoni, Himani; Singh, Saumya; Sharma, Promila; Waheed, Syed Mohsin (Asian Journal of Pharmaceutical and Clinical Research, 2016)
The present study deals with exploration of various beneficial potential of Emblica officinalis and Terminalia bellirica fruit extracts which includes phytochemical analysis and evaluation of total phenolics content (TPC), total flavonoids content (TFC) and antimicrobial activity. The antioxidant activity of the extracts was examined using diphenylpicrylhydrazyl (DPPH), TPC and TFC assay. The antimicrobial activity of the extracts was evaluated by agar well diffusion assay. Although, the extracts prevented the growth of both Gram positive and Gram negative bacteria. The EOA and EOM extracts both exhibit tannins, saponins, phenols and carbohydrates whereas, alkaloids and flavonoids are found only in EOM, and glycosides showed their presence in aqueous extract only. In contrast, TBA and TBM extracts, both contains alkaloids, tannins, coumarins, flavonoids and phenols. While carbohydrates are present barely in TBM, and TBA extract showed the presence of saponins and glycosides. The TPC results show that EOM (528±.013) has highest phenolic content in it followed by EOA (509±.003), TBM (284±.06) and TBA (280±.036). In TFC analysis too EOM (154±0) showed a higher concentration range of flavonoids followed by EOA (142±0),TBM (126±.017) and TBA (119±.007). In DPPH scavenging assay EOM (86.88±.310) showed maximum % inhibition followed by EOA (85.32±.414), TBM (80.57±.569) and TBA (75.55±.362) respectively. Antibacterial assay showed varying results for different bacterial strains such as, for EOA (10±1) demonstrated highest inhibition against E. coli, EOM (11.5±0.5) exhibited maximum inhibition against S. aureus, for K. pneumoniae EOA (13±2) displayed maximum inhibition and in case P. aeruginosa too EOA (12.5±0.5) showed maximum inhibition while TBM and TBA too showed significant amount of inhibition against test bacterial strains. The antibacterial and antioxidant activities of the extracts were found to be positively associated with the total phenolic and flavonoid content of the extracts. This study was conducted to identify the phytochemical composition of the fruit extracts of the two plants, their antioxidant and antibacterial potential, alongwith their neuroprotective and nootropic role. In order to establish their neuroprotective role, acute toxicity study was conducted on wistar rats to establish the safety of the extracts. The current study demonstrates and compares the antioxidant, antibacterial activities of the fruit extracts of Terminalia bellirica and Emblica officinalis and acute toxicity study further demonstrates that the extracts used are safe to conduct neuroprotective studies. Keywords: TPC(Total phenolic content), TFC(Total flavonoids content), EOM (Emblica officinalis Methanolic fruit extract), EOA(Emblica officinalis aqueous fruit extract) TBM (Terminalia bellirica Methanolic fruit extract) and TBA (Terminalia bellirica aqueous fruit extract).